THE EFFECT ADDITION OF LSWR INTO FUEL OILS AGAINST ALTERATION ITS PHYSICALS AND CHEMICALS PROPERTIES - Djainuddin Semar; Nur Ahadiat (Scientific Contributions Oil and Gas, 2007)
To fulfill yearly increase National demand for fuel oils (FO), therefor this paperconducted to researched the posibility added low sulfur wax residue (LSWR) into Nationalfuel oil comersial to some percentage volume againts its characteristic changes.Base on its pour point, the fuel oils modification formula, named FO-90 that has pourpoint 90oF, this formula content 6% volume LSWR.The laboratory test result, shown that nearly all characteristic fuel oils modification isconform with current domestic fuel oils specification 2, issued by Directorate GeneralOils and Gas on behalf of Indonesian goverment in their SK No. 03/P/DM/MIGAS/1986dated April 14, 1986.This paper proposes fuel oils specification, as input for government policy in reformulationof Indonesian fuel oils specification which confirm with international fuel oil specification.